Structural, Electronic, Elastic, Mechanical, and Opto-Electronic Properties for ZnAg2SnS4 and ZnAg2Sn0.93Fe0.07S4 Photocatalyst Effort on Wastewater Treatment through the First Principle Study - Mohammad Jahidul Islam; Md. Sabbir Hasan Sohag; Unesco Chakma; Ajoy Kumer; Md. Monsur Alam; Mohammed Nazrul Islam Khan (Advances in Condensed Matter Physics)
The stannite structured ZnAg2SnS4 was developed from its parent composition ZnAg2GeS4, which is considered to be an excellent photocatalytic material, as the demands for photocatalytic effect on organic and waste water treatment have been increasing around the globe. First and foremost, the geometry optimization was performed by density functional theory (DFT) of the generalized gradient approximation (GGA) with Perdew–Burke–Ernzerhof (PBE)-ballpark figured as the successful candidate for computational screening containing heavy metal complexes. The structural geometry parameters were determined along with the electronic band structure, density of state (DOS), partial density of state (PDOS), Mulliken charge population, elastic constant, and optical characteristics. When the Ge (ZnAg2GeS4) atom has been swapped out by a Sn (ZnAg2SnS4) atom, the changes in band gap is noticeable, which rises from 0.94 eV to 1.15 eV with the same geometry and surface area. But, after 7% Fe doping, it has decreased to 0.32 eV. The PDOS demonstrates that the production of hydrogen for photocatalytic influence on wastewater treatment is dependent on the Fe atom's ability to induce and boost the electron density in both the conduction band and the valence band. The study of the elastic constant and mechanical constant revealed that these crystals are extremely stable in any environment. The dielectric constant and optical absorptions illustrate the superior evidence for photocatalytic activity. To sum up, it could be said that after doping of Fe, the elastic constant and mechanical constant show all universal anisotropic index crystals and ZnAg2Sn0.93Fe0.07S4 can absorb a variety of UV radiation, which raises the possibility that it could function as a photocatalyst.